ІНТЕЛЕКТУАЛЬНІ РЕСУРСИ ДЕРЖАВНОГО УПРАВЛІННЯ: ОСОБЛИВОСТІ ВИКОРИСТАННЯ ТА ВІДТВОРЕННЯ (World Science, 2019)
The article deals with the managing process of the formation, development and reproduction of national intellectual resources of public administration (IRPA), which includes their use and reproduction; their structure and their function characteristics are revealed; the author's definition of the concept of "national intellectual resource of public administration" is proposed; the importance of managing national intellectual resources of public administration for modern public-management practice is characterized. It is argued that the peculiarity of national IRPAs lies in their flexibility, in that the process of their formation takes place in a separate national- cultural space, which is influenced by historical, political, educational, information and other factors. It is proved that the management of the national IRPA is a process of purposeful influence on the components of the national IRPA, their interaction in order to secure the state's advantages in the modern world or to achieve its development goals. The factors that determine the need for the formation, development, use and reproduction of national IRPA s are revealed.